Tricks with “a Sad Ring”:: The Endings of Alice Munro’s “The Ottawa Valley” - Ware, Tracy (Studies in Canadian Literature, 2006)
In a 1981 interview with J.R. (Tim) Struthers, Alice Munro says that "The stories in Something I've Been Meaning to Tell You are nearly all holding-pattern stories, except for ... 'The Ottawa Valley,' and that was a big turning-point story." Later she modifies that opinion ("scratch that holding-patterns business"), saying, "The truth is, one becomes very dissatisfied with everything." When Struthers notes the importance of such dissatisfaction, Munro agrees: "It's in 'The Ottawa Valley,' I believe. The last paragraph in this book is all about dissatisfaction with art" (28). That commentary raises several important questions. If the inadequacy of her representation of "real lives" matters, then how can she maintain (in the same interview) that those who dispute her accuracy demonstrate "a total confusion about what fiction is" (33)? And why does she say that the conclusion of "The Ottawa Valley" deals with a general "dissatisfaction with art" when it actually makes a different point? The answers to these questions involve autobiographical connections: as Munro states in her Paris Review interview, "The material about my mother is my central material in life" ("Art" 237), and therefore the ending of "The Ottawa Valley" does express a "dissatisfaction with art." For her, the writer must be free to use "bits of what is real," however "presumptuous" that sounds. Munro's commentaries tend to divert attention from the painfully vivid memories that give her work its force in favour of less volatile metafictional issues.